2020
DOI: 10.1088/1757-899x/890/1/012113
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate model of construction project operational efficiency

Abstract: Economic efficiency during the entire life cycle of a property is crucial when making a decision on an investment. The resulting performance indicators are influenced by various underlying factors. The purpose of the study is to determine the degree of the factors influence on the final result. The study considers an apartment building and 50 variants of the project implementation according to the chosen factors, which are construction period, selling price per square meter, discount rate, land plot cost and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The regional administration is actively involved in the project «School of the competent consumer» of the «United Russia» party, it educates citizens in the field of housing and communal services. In 2020, within the framework of this project, 78 training seminars were held, information materials and booklets were published [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The regional administration is actively involved in the project «School of the competent consumer» of the «United Russia» party, it educates citizens in the field of housing and communal services. In 2020, within the framework of this project, 78 training seminars were held, information materials and booklets were published [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…-the poor predictability of the innovative projects results, because the expected results of an innovative project can be predicted only at short time intervals [14];…”
Section: Methodsmentioning
confidence: 99%
“…Despite numerous studies of the concept of sustainable development, some authors criticize it;the information can be found in the works of S. Kwatra, A. Kumar, P. Sharma [19]. The authors touched upon the problems and prospects of the field of operational services and construction efficiency: Romanova A. I., Zagidullina G. M., Afanasyeva A. N., Hkairetdinova R. S. [20] and Elvira Shagiakhmetova other [21,22]. However, despite the presence of a broad theoretical and methodological generalization and practical solutions, there is a lack of practical examples demonstrating the effectiveness of modern solutions to the problem of optimizing the operational services of an apartment building and increasing the level of their smart management.…”
Section: Introductionmentioning
confidence: 99%